Selection of Newly Identified Growth-Promoting Archaea Haloferax Species With a Potential Action on Cobalt Resistance in Maize Plants - Selim, Samy; Akhtar, Nosheen; Hagagy, Nashwa; Alanazi, Awadh; Warrad, Mona; El Azab, Eman; Elamir, Mohammed Yagoub Mohammed; Al-Sanea, Mohammad M.; Jaouni, Soad K. Al; Abdel-Mawgoud, Mohamed; Shah, Anis Ali; Abdelgawad, Hamada (Frontiers in Plant Science, 2022)
Soil contamination with cobalt (Co) negatively impacts plant growth and production. To combat Co toxicity, plant growth-promoting microorganisms for improving plant growth are effectively applied. To this end, unclassified haloarchaeal species strain NRS_31 (OL912833), belonging to Haloferax genus, was isolated, identified for the first time, and applied to mitigate the Co phytotoxic effects on maize plants. This study found that high Co levels in soil lead to Co accumulation in maize leaves. Co accumulation in the leaves inhibited maize growth and photosynthetic efficiency, inducing oxidative damage in the tissue. Interestingly, pre-inoculation with haloarchaeal species significantly reduced Co uptake and mitigated the Co toxicity. Induced photosynthesis improved sugar metabolism, allocating more carbon to defend against Co stress. Concomitantly, the biosynthetic key enzymes involved in sucrose (sucrose-P-synthase and invertases) and proline (pyrroline-5- carboxylate synthetase (P5CS), pyrroline-5-carboxylate reductase (P5CR)) biosynthesis significantly increased to maintain plant osmotic potential. In addition to their osmoregulation potential, soluble sugars and proline can contribute to maintaining ROS hemostasis. Maize leaves managed their oxidative homeostasis by increasing the production of antioxidant metabolites (such as phenolics and tocopherols) and increasing the activity of ROS-scavenging enzymes (such as POX, CAT, SOD, and enzymes involved in the AsA/GSH cycle). Inside the plant tissue, to overcome heavy Co toxicity, maize plants increased the synthesis of heavy metal-binding ligands (metallothionein, phytochelatins) and the metal detoxifying enzymes (glutathione S transferase). Overall, the improved ROS homeostasis, osmoregulation, and Co detoxification systems were the basis underlying Co oxidative stress, mitigating haloarchaeal treatment's impact.